Ventilatory Failure And Pulmonary Embolism In Covid-19 Requiring Enhanced Venous Drainage For Extracorporeal Membrane Oxygenation - Talha, Khawaja M. (2023)
COVID-19 infection manifests as a spectrum of respiratory and vascular complications, including acute respiratory distress syndrome (ARDS) and pulmonary embolism. Herein, we describe a case of a healthy young male who presented with ARDS refractory to mechanical ventilation and concomitant bilateral pulmonary emboli managed with extracorporeal membrane oxygenation (ECMO) and embolectomy. The embolectomy and initial veno-venous ECMO configuration failed to correct the patient’s hypoxemia despite maximal flows. This was thought to be due to a high-output state secondary to vasodilatory shock preventing adequate drainage from the existing single drainage ECMO cannulation, following which a second venous cannula was placed to form a unique veno-veno-venous ECMO circuit that resolved the persistent hypoxemia. The case underscores the importance of identifying embolic events and vasodilatory shock in COVID-19 patients, both of which need to be addressed simultaneously to avoid worsening right ventricular failure (via both mechanical and hypoxia-driven pathways) and the resulting veno-arterial ECMO along with its associated complications.